Drug-Induced Interstitial Lung Disease - Wei-I Lee; Pravin Hissaria (Indian Journal of Rheumatology)
Drug-induced interstitial lung disease (DIILD) represents a rare but potentially fatal adverse drug reaction. A large number of drugs have been implicated to have this potential risk, including chemotherapeutics and disease-modifying antirheumatic drugs. The clinical presentations, laboratory investigations, pulmonary function test result, and imaging and histopathological findings associated with drug-induced pulmonary fibrosis are nonspecific. The diagnosis is achieved after the exclusion of alternative diagnosis, such as infection, pulmonary edema, and connective tissue diseases. However, sometimes, the underlying diseases (e.g., rheumatoid arthritis) and the drugs used to treat the disease (e.g., methotrexate) can both cause ILD; it is often difficult to tease out causality especially if baseline pulmonary assessment (respiratory function test and imaging) is incomplete prior to the commencement of the drug therapy. Many efforts have been put into investigating the pathogenesis of the DIILD, particularly as animal model of bleomycin-induced pulmonary fibrosis has been used as a surrogate for idiopathic pulmonary fibrosis. However, more research is required to improve our understanding of pathogenesis in order to develop more sensitive and specific diagnostic tests as well as to establish evidence-based treatment approach.